Social Order in Multiagent Systems - Conte, Rosaria; Dellarocas, Chris (Springer US, 2001)
Social Order in Multiagent Systems provides an overview of current approaches, problems, and considerations related to the study of norms and institutions in the context of multiagent systems. The contributions in this volume share the assumption that norms and other social institutions are of vital importance for the development of multiagent systems and agent-mediated interaction. Both formal and computational models of norms and normative systems are presented, including formal analysis of normative concepts and foundational models of norms; agent and systems architectures for implementing norms; and implemented systems. Social Order in Multiagent Systems is an excellent reference for researchers in artificial intelligence and computer science, and can be used as text for advanced level courses in multiagent systems
Keywords: Artificial Intelligence; Computer Science, general; Artificial intelligence; Computer science; Mehragentensystem; Konferenzschrift -- 2000 -- Barcelona